Literature Review: Penggunaan Dana BOS untuk Pengadaan Sarana dan Prasarana Sekolah - Suci Handhayani; Imamatul Mustafiah; Indah Putri Yani; Dela Septia; Fat-Thahillah Candra At-Toriq; Bahtiyar Heru Susanto (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Technological developments influence the development of schools in Indonesia regarding the facilities and learning media used, especially in the procurement of school facilities and infrastructure which must be met and improved. Procurement of school facilities and infrastructure still requires clear and sufficient funding sources. One of the funds that can be used as a source is BOS funds which are used to fund all school operations and non-operations, one of which is for facilities and infrastructure. The use of these funds needs to be planned so that they are sufficient according to the funds and expenses. Facilities and infrastructure that have been met can be put to good use to support the smooth running of learning and attention must be paid to their maintenance.